Low-temperature positive electrode material and preparation method thereof, positive plate and lithium ion battery
By using a low-temperature cathode material composed of a matrix material and a coating layer, the problem of reduced performance and high cost of lithium-ion batteries in low-temperature environments is solved, excellent low-temperature and high-temperature performance is achieved, the cobalt element content is reduced, and the cost is reduced.
Patent Information
- Application Number
- CN202411420619.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Lithium-ion batteries show performance reduction and safety risks in low-temperature environments. The existing cathode materials are costly while improving low-temperature performance and insufficient high-temperature storage performance.
The low-temperature positive electrode material composed of substrate materials and overwriting layers is the preparation method of lixniycozmn1-y-zaqo2-T. Control the micro -structure and composition of the material to achieve excellent low temperature and high temperature performance.
The optimization of low -temperature charge discharge performance is achieved, reducing the content of cobalt elements, reducing costs, and excellent high temperature storage performance.
Smart Images

Figure BDA0005080666620000141 
Figure BDA0005080666620000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a low-temperature positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, low self-discharge rate, no memory effect, fast charging capability, environmentally friendly recyclability, and low risk of spontaneous combustion, and have been widely used in 3C consumer products and power batteries. With the continuous advancement of science and technology, lithium-ion batteries will continue to play an important role.
[0003] However, in winter, especially when the temperature drops below -20℃ in the north, the viscosity of the electrolyte increases and the diffusion rate of lithium ions in the electrode material deteriorates, which greatly reduces the performance of lithium-ion batteries. Charging at low temperatures will cause lithium deposition, which seriously affects the safety performance of lithium-ion batteries. In addition, polarization is too large at low temperatures, and discharge easily reaches the cut-off voltage, resulting in reduced battery life.
[0004] Positive electrode materials play a vital role in lithium-ion batteries, which directly determine the energy density, safety and overall performance of the battery. In order to improve the low-temperature charge and discharge performance of positive electrode materials, the existing technology achieves this by improving the conductivity of the material, such as increasing the content of the Co element. Although increasing the content of the Co element can improve the low-temperature performance to a certain extent, Co resources are relatively scarce, and increasing the Co element content will lead to an increase in the cost of the positive electrode material. Therefore, it is of great significance to provide a low-cost positive electrode material with good low-temperature performance.
[0005] In addition, with the large-scale application of lithium-ion batteries, higher requirements are placed on the high-temperature storage performance of cathode materials. The insufficient high-temperature storage performance of conventional cathode materials limits the application of lithium-ion batteries.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The first object of the present invention is to provide a low-temperature positive electrode material which has low cost and exhibits excellent low-temperature charge and discharge performance, which is conducive to the further promotion and use of lithium-ion batteries.
[0008] The second object of the present invention is to provide a method for preparing a low-temperature positive electrode material, which has the advantages of simple operation, short process, low cost, and suitability for mass production.
[0009] A third object of the present invention is to provide a positive electrode sheet that exhibits excellent charge and discharge performance at low temperatures.
[0010] A fourth object of the present invention is to provide a lithium ion battery having excellent low temperature performance.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] The present invention first provides a low-temperature positive electrode material, which comprises a base material and a coating layer coated on the surface of the base material.
[0013] The general formula of the matrix material is Li x Ni y Co z Mn 1-y-z A q O 2-t , wherein 0.98≤x≤1.05, 0.55≤y≤0.75, 0.02≤z≤0.15, 0≤q≤0.01, 0≤t≤0.03, and A includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta elements.
[0014] The coating layer contains Q element, wherein Q includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta.
[0015] The raw materials for preparing the low-temperature positive electrode material include nickel-cobalt-manganese hydroxide precursor material, and the nickel-cobalt-manganese hydroxide precursor material includes a first precursor and a second precursor, the first precursor is mainly formed by heating and dehydrating the second precursor, the water content in the first precursor is ≤1500ppm, the water content in the second precursor is ≥2000ppm, and the mass ratio of the first precursor to the second precursor is n.
[0016] The morphology of the low-temperature positive electrode material is single crystal particles, the average size of the single crystal particles is r, the compaction density of the positive electrode sheet containing the low-temperature positive electrode material is PD, and n, r, PD and the particle size d of the low-temperature positive electrode material are related. 99 and particle size d min Satisfies the following relationship: 30≤(n×PD×d 99 ) / (d min ×r)≤100; where r is in μm, particle size d 99 The unit is μm, particle size d min The unit of is μm, and the unit of PD is g / cm 3 .
[0017] Furthermore, n=0.5-1.2.
[0018] Furthermore, said r=1.4-1.8 μm, and / or said r is measured by a scanning electron microscope.
[0019] Furthermore, the d 99 =9.0~15.0μm.
[0020] Furthermore, the d min =0.2~0.5μm.
[0021] Furthermore, the PD is 3.5 to 3.8 g / cm 3 .
[0022] Furthermore, the water content in the first precursor is 500-1500 ppm.
[0023] Furthermore, the water content in the second precursor is 2000-5000 ppm.
[0024] The present invention further provides a method for preparing the low-temperature positive electrode material, comprising the following steps: heating and dehydrating a second precursor to obtain a first precursor; mixing the first precursor, the second precursor, a lithium source and a first additive and calcining the mixture to obtain a matrix material; the first additive comprises an A element, wherein A comprises at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta; mixing the matrix material and the second additive and sintering the mixture to obtain the low-temperature positive electrode material; the second additive comprises an Q element, wherein Q comprises at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta.
[0025] Furthermore, the temperature of the heating dehydration is 100-150° C., and / or the time of the heating dehydration is 1-3 hours.
[0026] Furthermore, the calcination temperature is 850-950°C.
[0027] Furthermore, the calcination holding time is 8 to 16 hours.
[0028] Furthermore, the calcination further includes a crushing step.
[0029] Furthermore, the sintering temperature is 300-600° C., and / or the sintering holding time is 3-7 hours.
[0030] The present invention further provides a positive electrode sheet, comprising the low-temperature positive electrode material.
[0031] The present invention also provides a lithium ion battery, comprising the positive electrode sheet.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The low-temperature positive electrode material provided by the present invention has high kinetics and high stability, and exhibits excellent low-temperature charge and discharge performance at low temperatures. In addition, the low-temperature positive electrode material has a low cobalt content and low cost.
[0034] (2) The low-temperature positive electrode material provided by the present invention has excellent high-temperature storage performance. DETAILED DESCRIPTION
[0035] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0036] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0037] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0038] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0039] In a first aspect, the present invention provides a low-temperature positive electrode material, comprising a base material and a coating layer coated on the surface of the base material;
[0040] The general formula of the matrix material is Li x Ni y Co z Mn 1-y-z A q O 2-t .
[0041] Among them, 0.98≤x≤1.05, 0.55≤y≤0.75, 0.02≤z≤0.15, 0≤q≤0.01, 0≤t≤0.03. Specifically, x includes but is not limited to any point value of 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, 1.05 or any range value between two of them; y includes but is not limited to any point value of 0.55, 0.58, 0.60, 0.62, 0.65, 0.67, 0.7, 0.73, 0.75 or any range value between two of them; z includes but is not limited to 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.11, 0.12, 0.13, 0.14 , 0.015, or any range between them; q includes but is not limited to any one of 0, 0.001, 0.002, 0.003, 0.005, 0.006, 0.008, 0.009, 0.01, or any range between them; t includes but is not limited to any one of 0, 0.001, 0.002, 0.003, 0.005, 0.006, 0.008, 0.009, 0.01, 0.015, 0.02, 0.025, 0.03, or any range between them.
[0042] A is a doping element, and A includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta elements, preferably at least two, and more preferably at least three.
[0043] In some specific implementations, in order to further improve the low temperature performance of the positive electrode material, 0 <q≤0.005。
[0044] The coating layer contains Q element, wherein Q includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta; preferably at least two, more preferably at least three.
[0045] The raw materials for preparing the low-temperature positive electrode material include a nickel-cobalt-manganese hydroxide precursor material, and the nickel-cobalt-manganese hydroxide precursor material includes a first precursor and a second precursor, and the first precursor is mainly formed by heating and dehydrating the second precursor. That is, the water content in the second precursor is greater than the water content in the first precursor. The water content in the first precursor is ≤1500ppm, the water content in the second precursor is ≥2000ppm, and the mass ratio of the first precursor to the second precursor is n, that is, n:1. Among them, the water content in the first precursor includes but is not limited to any one of 1500ppm, 1300ppm, 1200ppm, 1000ppm, 800ppm, 600ppm, 500ppm, 300ppm, 100ppm or any range value between the two. The water content in the second precursor includes, but is not limited to, any one of 2000 ppm, 2200 ppm, 2500 ppm, 2800 ppm, 3000 ppm, 3500 ppm, 4000 ppm, 4500 ppm, 5000 ppm, and 6000 ppm, or a range between any two of them.
[0046] The morphology of the low-temperature positive electrode material is a single crystal particle, the average size of the single crystal particle is r, and the compaction density of the positive electrode sheet containing the low-temperature positive electrode material is PD, wherein n, r, PD and the particle size d of the low-temperature positive electrode material are 99 and particle size d min Satisfies the following relationship: 30≤(n×PD×d 99 ) / (d min ×r)≤100.
[0047] In the above relationship, r is in μm, particle size d is 99 The unit is μm, particle size d min The unit of is μm, and the unit of PD is g / cm 3 .
[0048] The low-temperature positive electrode material provided by the present invention has high kinetics and high stability, and the positive electrode material exhibits excellent low-temperature charge and discharge performance at low temperatures.
[0049] In addition, the low-temperature positive electrode material has a low cobalt content and low cost.
[0050] The low-temperature positive electrode material provided by the present invention solves the technical problem that the prior art cannot take both cost and low-temperature performance into consideration.
[0051] In addition, the low-temperature positive electrode material provided by the present invention has excellent high-temperature storage performance.
[0052] The present invention controls (n×PD×d 99) / (d min ×r) in the range of 30 to 100 can significantly improve low temperature kinetics. 99 ) / (d min ×r) is too small, the proportion of small-sized particles is small, which cannot meet the role of improving low-temperature kinetics; when (n×PD×d 99 ) / (d min When the value of ×r) is too large, the proportion of small-sized particles is too high, and long-term and high-temperature stability cannot be taken into account.
[0053] In some specific embodiments, the general formula of the nickel-cobalt-manganese hydroxide precursor material is Ni a Co b Mn 1-a-b (OH)2. Wherein, 0.55≤a≤0.75, including but not limited to any one of 0.55, 0.58, 0.60, 0.62, 0.65, 0.67, 0.7, 0.73, 0.75 or any range between two of them; 0.02≤b≤0.15, including but not limited to any one of 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15 or any range between two of them.
[0054] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, n=0.5-1.2, including but not limited to any point value of 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or a range value between any two of them.
[0055] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, the r=1.4~1.8μm, including but not limited to any point value of 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm or a range value between any two of them.
[0056] In some specific embodiments, the r is measured by scanning electron microscopy.
[0057] In some specific embodiments, the testing method of r is as follows: use a scanning electron microscope (SEM) to take a photo of the positive electrode material with a magnification of 5000 times, measure the length and width of the particles in the field of view, that is, perform longitudinal and transverse size measurements respectively, and then take the average value of the longitudinal size and the transverse size, which is the actual size of a particle. After measuring the sizes of several (for example, 200 to 500) particles, take the average value of all measured values to obtain the average size r of the single crystal particles.
[0058] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, the d 99 =9.0~15.0μm, including but not limited to any point value of 9.0μm, 10.0μm, 11.0μm, 12.0μm, 13.0μm, 14.0μm, 15.0μm or the range value between any two of them.
[0059] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, the d min =0.2-0.5 μm, including but not limited to any point value of 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm or a range value between any two of them.
[0060] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, the PD is 3.5-3.8 g / cm 3 , including but not limited to 3.5g / cm 3 、3.55g / cm 3 、3.6g / cm 3 、3.65g / cm 3 、3.7g / cm 3 、3.75g / cm 3 、3.8g / cm 3 Any point value in or any range between them.
[0061] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, the water content in the first precursor is 500-1500 ppm, including but not limited to any point value of 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm, 1200 ppm, 1300 ppm, 1500 ppm or any range value between two of them.
[0062] In some specific embodiments, in order to further improve the low temperature performance and high temperature storage performance of the positive electrode material, the water content in the second precursor is 2000-5000 ppm, including but not limited to any point value of 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm or a range value between any two of them.
[0063] In some specific embodiments, the test method for the electrode compaction density PD of the positive electrode sheet containing the low-temperature positive electrode material is as follows: the finished electrode sheet is rolled at a pressure of 20 MPa for 2 minutes, the thickness and mass of the electrode sheet are measured, and the compaction density of the electrode sheet can be calculated.
[0064] In some specific embodiments, the mass of the coating layer accounts for 0.5% to 2% of the mass of the base material, including but not limited to any point value of 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.8%, 2% or a range between any two of them.
[0065] In a second aspect, the present invention provides a method for preparing the low-temperature positive electrode material, which specifically comprises the following steps:
[0066] The second precursor is heated and dehydrated to obtain the first precursor. Dehydration here refers to reducing the water content in the second precursor.
[0067] The first precursor, the second precursor, the lithium source and the first additive are mixed and calcined to obtain a matrix material. The first additive includes an A element, wherein A includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta. It can be understood that the first additive is a dopant.
[0068] The base material is mixed with a second additive and then sintered to obtain the low-temperature positive electrode material. The second additive includes a Q element, wherein Q includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta. It is understandable that the second additive is a coating agent.
[0069] The method for preparing the low-temperature positive electrode material provided by the present invention has the advantages of simple operation, short process, low cost, and mass production.
[0070] In some specific embodiments, the lithium source includes any lithium-containing compound commonly used in the art, such as lithium carbonate, lithium hydroxide, etc., but is not limited thereto.
[0071] In some specific embodiments, the second precursor has the same molecular formula as the first precursor, which is Ni a Co b Mn 1-a-b(OH)2. Wherein, 0.55≤a≤0.75, including but not limited to any one of 0.55, 0.58, 0.60, 0.62, 0.65, 0.67, 0.7, 0.73, 0.75 or any range between two of them; 0.02≤b≤0.15, including but not limited to any one of 0.02, 0.03, 0.04, 0.05, 0.06, 0.08, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15 or any range between two of them.
[0072] In some specific embodiments, the first additive includes a compound containing A, such as an oxide, a hydroxide or a salt thereof. Wherein A includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta.
[0073] In some specific embodiments, the second additive includes a compound containing Q, such as an oxide, a hydroxide or a salt thereof, wherein Q includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta.
[0074] In some specific embodiments, in order to further improve the low-temperature performance and high-temperature storage performance of the positive electrode material, the first additive and the second additive contain different element types.
[0075] In some specific embodiments, the mass of the second additive accounts for 0.5% to 2% of the mass of the base material, including but not limited to any point value of 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.8%, 2% or a range between any two of them.
[0076] In some specific embodiments, the temperature of the heating dehydration is 100-150°C, including but not limited to any point value of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or a range between any two of them.
[0077] In some specific embodiments, the heating dehydration is performed in a dry atmosphere.
[0078] In some specific embodiments, the heating dehydration time is 1 to 3 hours, including but not limited to any one of 1 hour, 1.5 hours, 2 hours, 2.5 hours, and 3 hours, or a range between any two of them.
[0079] In some specific embodiments, the calcination temperature is 850-950°C, including but not limited to any point value of 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 910°C, 920°C, 930°C, 950°C or a range value between any two of them.
[0080] In some specific embodiments, the calcination holding time is 8 to 16 hours, including but not limited to any one of 8 hours, 10 hours, 12 hours, 13 hours, 15 hours, and 16 hours, or a range between any two of them.
[0081] In some specific embodiments, the calcination atmosphere includes air atmosphere and / or oxygen atmosphere.
[0082] In some specific embodiments, the calcination further comprises a pulverizing step. Preferably, the pulverizing step comprises air flow pulverizing. The particles are dispersed into single crystal particles by air flow pulverizing.
[0083] In some specific embodiments, the sintering temperature is 300-600°C, including but not limited to any point value of 300°C, 350°C, 400°C, 450°C, 500°C, 600°C or a range between any two of them.
[0084] In some specific embodiments, the sintering holding time is 3 to 7 hours, including but not limited to any one of 3 hours, 4 hours, 5 hours, 6 hours, and 7 hours, or a range between any two of them.
[0085] In some specific embodiments, the sintering atmosphere includes air atmosphere and / or oxygen atmosphere.
[0086] In a third aspect, the present invention provides a positive electrode sheet comprising the low-temperature positive electrode material.
[0087] The positive electrode sheet exhibits excellent charge and discharge performance at low temperatures.
[0088] Optionally, the positive electrode sheet further includes a binder and / or a conductive agent, which is not limited in the present invention.
[0089] In a fourth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet.
[0090] The lithium-ion battery has excellent low-temperature performance, low cost, and good high-temperature storage performance.
[0091] Optionally, the lithium-ion battery further includes a negative electrode sheet, an electrolyte and a separator, which is not limited in the present invention.
[0092] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0093] Example 1
[0094] The low-temperature positive electrode material provided in this embodiment includes a base material and a coating layer coated on the surface of the base material. The general formula of the base material is Li 1.00 Ni 0.55 Co 0.05 Mn 0.4 Mg 0.003 Sr 0.002 Mo 0.001 O 2.0065 The main components of the coating layer are Nb2O5 and Ta2O5. The preparation method of the low-temperature positive electrode material comprises the following steps:
[0095] (1) The second precursor Ni 0.55 Co 0.05 Mn 0.4 (OH)2 was heated and dehydrated at 125℃ for 1h in a dry atmosphere to obtain the first precursor Ni 0.55 Co 0.05 Mn 0.4 (OH) 2. The water content in the first precursor is 1622 ppm, and the water content in the second precursor is 3259 ppm.
[0096] (2) According to the ratio in the target chemical formula, the first precursor, the second precursor, lithium hydroxide, MgO, SrO, and MoO2 are uniformly mixed, wherein the mass ratio n of the first precursor to the second precursor is 0.5 (i.e., 0.5:1). Then, the mixture is calcined at 900° C. for 12 h in an air atmosphere, and after cooling, the particles are dispersed into single crystal particles by air flow pulverization to obtain a matrix material.
[0097] (3) The above-mentioned matrix material is uniformly mixed with Nb2O5 and Ta2O5, wherein the mass of Nb2O5 accounts for 0.5% of the mass of the matrix material, and the mass of Ta2O5 accounts for 0.3% of the mass of the matrix material, and then sintered at 350°C for 7h in an air atmosphere to obtain a low-temperature positive electrode material.
[0098] The morphology of the low-temperature positive electrode material prepared in this embodiment is single crystal particles, and the average size r of the single crystal particles and the particle size d of the low-temperature positive electrode material are 99 , particle size d of low temperature cathode material minThe results of the compacted density PD of the positive electrode sheet made of the low-temperature positive electrode material are shown in Table 1. Define (n×PD×d99) / (dmin×r)=DR, and the calculation results of DR are shown in Table 1, where r is in μm and particle size d is 99 The unit is μm, particle size d min The unit of is μm, and the unit of PD is g / cm 3 .
[0099] Among them, the test method for the average size r of single crystal particles of low-temperature positive electrode materials is as follows: use a scanning electron microscope (SEM) to take a photo of the positive electrode material with a magnification of 5000 times, measure the length and width of the particles in the field of view, that is, measure the longitudinal and lateral dimensions respectively, and then take the average value of the longitudinal and lateral dimensions, which is the actual size of a particle. After measuring the sizes of several (300) particles, take the average of all measured values to obtain r.
[0100] The test method for the compaction density PD of the positive electrode sheet made of low-temperature positive electrode material is as follows: roll the finished electrode sheet under a pressure of 20MPa for 2min, measure the thickness and mass of the electrode sheet, and then calculate the compaction density of the electrode sheet.
[0101] The preparation method of the positive electrode sheet made of low-temperature positive electrode material is as follows: the low-temperature positive electrode material is uniformly mixed with conductive carbon black SuperP, carbon nanotubes CNT, polyvinylidene fluoride PVDF and N-methylpyrrolidone NMP in a mass ratio of 97.2:1.0:0.8:1.0:100 to obtain a slurry, and then the slurry is uniformly coated on an aluminum foil and dried to obtain a positive electrode sheet.
[0102] Example 2-Example 7
[0103] The preparation methods of the low-temperature positive electrode materials provided in Examples 2 to 7 are basically the same as those in Example 1, except that the heating and dehydration temperature, the heating and dehydration time, or the mass ratio n of the first precursor and the second precursor are different, as shown in Table 1 below.
[0104] The average size r of the single crystal particles of the low-temperature positive electrode material prepared in Example 2 to Example 7, and the particle size d of the low-temperature positive electrode material 99 , particle size d of low temperature cathode material min , the compacted density PD results of the positive electrode sheets made of various low-temperature positive electrode materials, and the DR values are shown in Table 1. Among them, the test methods of r and PD and the preparation method of the positive electrode sheet are the same as those in Example 1.
[0105] Example 8
[0106] The low-temperature positive electrode material provided in this embodiment includes a base material and a coating layer coated on the surface of the base material. The general formula of the base material is Li1.04 Ni 0.75 Co 0.13 Mn 0.12 Nb 0.005 Ta 0.002 B 0.002 O 2.029 The main components of the coating layer are SrO and MoO2. The preparation method of the low-temperature positive electrode material comprises the following steps:
[0107] (1) The second precursor Ni 0.75 Co 0.13 Mn 0.12 (OH)2 was heated and dehydrated at 145 °C for 2.5 h in a dry atmosphere to obtain the first precursor Ni 0.75 Co 0.13 Mn 0.12 (OH) 2. The water content in the first precursor is 614 ppm, and the water content in the second precursor is 2820 ppm.
[0108] (2) According to the ratio in the target chemical formula, the first precursor, the second precursor, lithium hydroxide, Nb2O5, Ta2O5, and B2O3 are uniformly mixed, wherein the mass ratio n of the first precursor to the second precursor is 1 (i.e., 1:1). Then, the mixture is calcined at 950° C. for 8 h in an air atmosphere, and after cooling, the particles are dispersed into single crystal particles by air flow pulverization to obtain a matrix material.
[0109] (3) The above-mentioned matrix material is uniformly mixed with SrO and MoO2, wherein the mass of SrO accounts for 0.4% of the mass of the matrix material, and the mass of MoO2 accounts for 0.8% of the mass of the matrix material, and then sintered at 450°C for 4h in an air atmosphere to obtain a low-temperature positive electrode material.
[0110] The morphology of the low-temperature positive electrode material prepared in this embodiment is single crystal particles, and the average size r of the single crystal particles and the particle size d of the low-temperature positive electrode material are 99 , particle size d of low temperature cathode material min The results of the compacted density PD of the positive electrode sheet made of the low-temperature positive electrode material and the calculation results of DR are shown in Table 1. The test methods of r and PD and the preparation method of the positive electrode sheet are the same as those in Example 1.
[0111] Example 9
[0112] The low-temperature positive electrode material provided in this embodiment includes a base material and a coating layer coated on the surface of the base material, wherein the chemical formula of the base material is the same as that of Example 1, and the main components of the coating layer are ZrO2, Al2O3 and WO3. The preparation method of the low-temperature positive electrode material is basically the same as that of Example 1, except that: in step (3), Nb2O5 and Ta2O5 are replaced by ZrO2, Al2O3 and WO3, wherein the mass of ZrO2 accounts for 0.7% of the mass of the base material, the mass of Al2O3 accounts for 1% of the mass of the base material, and the mass of WO3 accounts for 0.3% of the mass of the base material.
[0113] The morphology of the low-temperature positive electrode material prepared in this embodiment is single crystal particles, and the average size r of the single crystal particles and the particle size d of the low-temperature positive electrode material are 99 , particle size d of low temperature cathode material min The results of the compacted density PD of the positive electrode sheet made of the low-temperature positive electrode material and the calculation results of DR are shown in Table 1. The test methods of r and PD and the preparation method of the positive electrode sheet are the same as those in Example 1.
[0114] Comparative Example 1
[0115] The preparation method of the low-temperature positive electrode material provided in this comparative example is basically the same as that of Example 1, except that the second precursor is not heated and dehydrated, that is, the first precursor is not added, but only the second precursor (n=0) is added according to the proportion of the target chemical formula.
[0116] The morphology of the low-temperature positive electrode material prepared in this comparative example is single crystal particles, and the average size r of the single crystal particles and the particle size d of the low-temperature positive electrode material are 99 , particle size d of low temperature cathode material min The results of the compacted density PD of the positive electrode sheet made of the low-temperature positive electrode material and the calculation results of DR are shown in Table 1. The test methods of r and PD and the preparation method of the positive electrode sheet are the same as those in Example 1.
[0117] Comparative Example 2-Comparative Example 5
[0118] The preparation methods of the low-temperature positive electrode materials provided in Comparative Examples 2 to 5 are basically the same as those in Example 1, except that the heating and dehydration temperature, the heating and dehydration time, or the mass ratio n of the first precursor and the second precursor are different, as shown in Table 1 below.
[0119] The average size r of the single crystal particles of the low-temperature positive electrode material prepared in Comparative Examples 2 to 5, and the particle size d of the low-temperature positive electrode material 99 , particle size d of low temperature cathode material min, the compacted density PD results of the positive electrode sheets made of various low-temperature positive electrode materials, and the DR values are shown in Table 1. Among them, the test methods of r and PD and the preparation method of the positive electrode sheet are the same as those in Example 1.
[0120] Table 1 Preparation parameters and performance parameters of low-temperature cathode materials
[0121]
[0122]
[0123] Experimental example
[0124] The low-temperature positive electrode materials prepared in each embodiment and each comparative example were used as positive electrode active materials to prepare soft-pack batteries according to the following method: the positive electrode active material, conductive carbon black Super P, carbon nanotubes CNT, polyvinylidene fluoride PVDF and N-methylpyrrolidone NMP were uniformly mixed in a mass ratio of 97.2:1.0:0.8:1.0:100 to obtain a positive electrode slurry, the positive electrode slurry was uniformly coated on aluminum foil, and dried to obtain a positive electrode sheet. The sheet was rolled to a compaction density of 3.45g / cm 3 , and a rolled positive electrode sheet is obtained. The negative electrode active material natural graphite, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose and the binder styrene butadiene rubber are mixed in a mass ratio of 96.4:1:1.2:1.4, and then the solvent deionized water is added and stirred thoroughly to obtain a negative electrode slurry. The negative electrode slurry is evenly coated on the copper foil, and after drying, cold pressing and slitting processes, a negative electrode sheet is obtained. Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 1:1:1 to form an organic solvent system, and then fully dried lithium hexafluorophosphate is dissolved in the organic solvent system to prepare an electrolyte with a concentration of 1 mol / L. The diaphragm is a porous film of polyethylene with a thickness of 11 μm. The above-mentioned rolled positive electrode sheet, negative electrode sheet, diaphragm and electrolyte are composed of a soft-pack battery with a capacity of 1Ah, and its electrical properties are measured according to the following method. The results are shown in Table 2.
[0125] The low temperature discharge performance test method is as follows: each soft pack battery cell is placed at 25°C, charged to 4.35V using a constant current of 0.33A, and then charged to a cut-off current of 50mA using a constant voltage of 4.35V; then discharged to 2.8V using a constant current of 0.33A, and the discharge capacity is recorded as the 25°C discharge capacity; the soft pack battery cell is placed at 25°C, charged to 4.35V using a constant current of 0.33A, and then charged to a cut-off current of 50mA using a constant voltage of 4.35V; then the soft pack battery cell is placed at -20°C for 3h to reach a stable state, and discharged to 2.5V using a constant current of 0.33A, and the discharge capacity is recorded as the -20°C discharge capacity. Low temperature discharge performance = -20°C discharge capacity / 25°C discharge capacity × 100%.
[0126] The high-temperature storage gas production test method is as follows: at room temperature, charge the battery to 4.35V at a rate of 0.33C, and use the drainage method to record the initial volume of the battery V1. Then store the battery in a 60℃ constant temperature oven. Every 7 days, take the battery out of the oven, let it stand at room temperature, test the battery volume, and record it as V7. Then charge the battery to 4.35V at a rate of 0.33C, and store the battery in a 60℃ constant temperature oven again. Every 7 days, take the battery out of the oven, let it stand at room temperature, test the battery volume, and record it as V x , where x is the number of days the battery has been stored (in Table 2, the battery has been stored for 28 days). By analogy, the volume change of the battery compared to V1 corresponds to the amount of gas generated by the battery cell during storage. The formula for calculating the gas generation of the battery is: (V x -V1) / V1×100%.
[0127] Table 2 Electrochemical performance test results
[0128] Group -20℃ discharge capacity / 25℃ discharge capacity (%) 28-day storage gas production (%) Example 1 72 5 Example 2 69 3 Example 3 71 1 Example 4 71 1 Example 5 68 6 Example 6 69 5 Example 7 70 3 Example 8 75 4 Example 9 73 2 Comparative Example 1 53 12 Comparative Example 2 59 11 Comparative Example 3 62 13 Comparative Example 4 53 10 Comparative Example 5 55 8
[0129] It can be seen from Table 1 and Table 2 that the positive electrode materials of Comparative Examples 1 to 5 do not satisfy 30≤(n×PD×d 99 ) / (d min ×r)≤100, resulting in poor low-temperature discharge performance and poor gas production performance.
[0130] Each embodiment satisfies 30≤(n×PD×d 99 ) / (d min ×r)≤100, the positive electrode material has good uniformity of particle distribution, good low-temperature charge and discharge performance, and excellent high-temperature storage performance.
[0131] Specifically, by comparing Example 1 with Example 2-Example 7, it can be seen that the heating and dehydration temperature, the heating and dehydration time, and the mass ratio n of the first precursor and the second precursor will affect the DR value, thereby affecting the low-temperature discharge performance and high-temperature storage performance.
[0132] In addition, by comparing Example 1 with Example 9, it can be seen that the composition of the coating layer and its mass ratio will also affect the low-temperature discharge performance and high-temperature storage performance of the battery.
[0133] In summary, the present invention can improve the low-temperature charge and discharge performance of the positive electrode material by controlling the cobalt content and reducing the cost of the positive electrode material, while also improving the high-temperature stability of the positive electrode material.
[0134] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A low-temperature positive electrode material, characterized in that: It comprises a base material and a coating layer coated on the surface of the base material; The general formula of the matrix material is Li x Ni y Co z Mn 1-y-z A q O 2-t , wherein 0.98≤x≤1.05, 0.55≤y≤0.75, 0.02≤z≤0.15, 0≤q≤0.01, 0≤t≤0.03, and A includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta elements; The coating layer contains Q element, wherein Q includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta; The raw material for preparing the low-temperature positive electrode material includes a nickel-cobalt-manganese hydroxide precursor material, and the nickel-cobalt-manganese hydroxide precursor material includes a first precursor and a second precursor, the first precursor is mainly formed by heating and dehydrating the second precursor, the water content in the first precursor is ≤1500ppm, the water content in the second precursor is ≥2000ppm, and the mass ratio of the first precursor to the second precursor is n; The morphology of the low-temperature positive electrode material is single crystal particles, the average size of the single crystal particles is r, the compaction density of the positive electrode sheet containing the low-temperature positive electrode material is PD, and n, r, PD and the particle size d of the low-temperature positive electrode material are related. 99 and particle size d min Satisfies the following relationship: 30≤(n×PD×d 99 ) / (d min ×r)≤100; where r is in μm, particle size d 99 The unit is μm, particle size d min The unit of is μm, and the unit of PD is g / cm 3 .
2. The low-temperature positive electrode material according to claim 1, characterized in that: The n=0.5~1.
2.
3. The low-temperature positive electrode material according to claim 1, characterized in that: The r=1.4-1.8 μm, and / or the r is measured by a scanning electron microscope.
4. The low-temperature positive electrode material according to claim 1, characterized in that: The d 99 =9.0~15.0μm.
5. The low-temperature positive electrode material according to claim 1, characterized in that: The d min =0.2~0.5μm.
6. The low-temperature positive electrode material according to claim 1, characterized in that: PD = 3.5-3.8 g / cm 3 .
7. The low-temperature positive electrode material according to claim 1, characterized in that: The water content in the first precursor is 500-1500 ppm.
8. The low-temperature positive electrode material according to claim 1, characterized in that: The water content in the second precursor is 2000-5000 ppm.
9. The method for preparing a low-temperature positive electrode material according to any one of claims 1 to 8, characterized in that: The steps include: The second precursor is heated and dehydrated to obtain a first precursor; the first precursor, the second precursor, a lithium source and a first additive are mixed and calcined to obtain a matrix material; the first additive includes an A element, wherein A includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta; The base material is mixed with a second additive and then sintered to obtain the low-temperature positive electrode material; the second additive includes a Q element, wherein Q includes at least one of Ti, Zr, Al, W, B, Mg, Sr, Mo, Nb and Ta.
10. The method for preparing a low-temperature positive electrode material according to claim 9, characterized in that: The temperature of the heating dehydration is 100-150° C., and / or the time of the heating dehydration is 1-3 hours.
11. The method for preparing a low-temperature positive electrode material according to claim 9, characterized in that: At least one of the following conditions is met: (1) The calcination temperature is 850-950° C.; (2) The calcination holding time is 8 to 16 hours; (3) The method further comprises a crushing step after the calcination.
12. The method for preparing a low-temperature positive electrode material according to claim 9, characterized in that: The sintering temperature is 300-600° C., and / or the sintering holding time is 3-7 hours.
13. A positive electrode sheet, characterized in that: It comprises the low-temperature positive electrode material as claimed in any one of claims 1 to 8.
14. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 13.
Citation Information
Patent Citations
Doped nickel cobalt lithium manganate precursor, preparation method thereof and doped nickel cobalt lithium manganate positive electrode material
CN113036119A
Lithium ion battery and preparation method thereof
CN113422044A
Dehydration system of lithium ion battery positive electrode material precursor and method for preparing positive electrode material precursor
CN114695880A
Monocrystal-coated polycrystal positive electrode material with core-shell structure and preparation method of single crystal-coated polycrystal positive electrode material
CN115377374A
Positive electrode material and preparation method thereof, positive electrode plate and secondary battery
CN117913268A
Cited By
Positive electrode material, positive plate and battery
CN120497319A